2007
DOI: 10.1080/11038120701208158
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome after cervical cone excision: a case‐control study

Abstract: Treatment by CLC and LEEP increases the risk of preterm delivery, low birth weight and pPROM in subsequent pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(14 citation statements)
references
References 37 publications
0
13
1
Order By: Relevance
“…Women diagnosed with CIN typically have a childbearing age and the median age of these patients has been reported to be from 34 to 40 years in previous studies [6,7,8,9]. However, the median age was 45 years in our study.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Women diagnosed with CIN typically have a childbearing age and the median age of these patients has been reported to be from 34 to 40 years in previous studies [6,7,8,9]. However, the median age was 45 years in our study.…”
Section: Discussioncontrasting
confidence: 54%
“…There are concerns about the increased risk of preterm delivery and other adverse pregnancy-related outcomes after a cervical excisional procedure [7,9]. For this reason, it is difficult to decide whether the ‘see-and-treat' strategy is the optimal method of treatment, although the accuracy of colposcopically directed biopsy itself has long been questioned [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sadler et al [14] already demonstrated that for excisions of 17 mm or more the risk of pPROM but not of PD was higher (RR 3.6, 95% CI 1.8–7.5), whereas Samson et al and Sjøborg et al, independently from depth of excision, after cervical laser conisation or loop electrosurgical excision procedure found an increased risk of both pPROM and PD [15, 16]. …”
Section: Resultsmentioning
confidence: 99%
“…When a follow-up test for women with negative biopsy has a high PPV for CIN2+, direct treatment is more suitable than re-biopsies for women older than 40 years of age if the triage test is positive. Given the impact of cervical treatment (such as LLETZ or conization) on pregnancy outcomes [19], [20], [35], [37], [39], [40], cervical treatment is more critical for women planning to have children. In addition, if a high-grade lesion is found in a woman above 40 years of age, there is a higher chance that the lesion has been present for a longer period of time, and at higher risk of progression [34], [41].…”
Section: Discussionmentioning
confidence: 99%